Analysis of Groundwater Chemical Characteristics and Spatiotemporal Evolution Trends of Influencing Factors in Southern Beijing Plain - Li, Chen; Men, Bao-Hui; Yin, Shi-Yang (Frontiers in Environmental Science, 2022)
In this study, the Daxing District was taken as a typical area to understand the evolution rules of the chemical characteristics of shallow groundwater in the plain areas of Beijing. By collecting monitoring data on shallow groundwater from 2006 to 2016, the spatiotemporal evolution trends of the chemical characteristics and influencing factors of shallow groundwater in Daxing District were studied using the ion combination ratio method, variation coefficient method and principal component analysis–partial connection number method. The results show the following: (1) The cations and anions of groundwater in the study area increased with time. (2) The maximum coefficient of variation was NO3− and the minimum was HCO3−, indicating that these two ions were influenced by human factors and natural factors, respectively. (3) The chemical types of groundwater were mainly HCO3–Ca, with little change in the short term. (4) The hydrochemical type and anion and cation components also changed accordingly with the change in NO3−, indicating the profound impact of NO3− on the evolution of groundwater components. (5) The results of the Gibbs diagram show that the natural origin of the groundwater components in the area was mainly rock weathering type, and the main cations and anions in groundwater were affected by natural factors and human factors. (6) The results of the ion combination ratio method show that Na+ mainly came from rock salt and silicate, whereas Ca2+ mainly came from gypsum and anhydrite. At the same time, the groundwater in the study area showed an ion exchange effect, which tended to increase with time. (7) According to the principal component analysis–partial connection number method, the groundwater has always been affected by human factors and natural factors. Natural factors have dominated, but the influence of human factors on hydrochemical components has been increasing. From the spatial distribution of the impact of human factors and natural factors on groundwater composition, regions with higher urbanisation degrees are highly affected by human factors and vice versa. This study can provide a theoretical and methodological reference for regional groundwater management and industrial layout.